Measuring Creative Self-Efficacy: An Item Response Theory Analysis of the Creative Self-Efficacy Scale - Shaw, Amy; Kapnek, Melissa; Morelli, Neil A. (Frontiers in Psychology, 2021)
Applying the Graded Response Model (GRM) within the Item Response Theory (IRT) framework, the present study analyzes the psychometric properties of the Creative Self-Efficacy scale (Karwowski, 2012, 2014; Karwowski, Lebuda, & Wiśniewska, 2018). With an ethnically diverse sample of U.S. college students, the results suggested that the 6 items of the CSE scale were well fitted to a latent unidimensional structure. The scale also had adequate measurement precision or reliability, high levels of item discrimination, and an appropriate range of item difficulty. Gender-based differential item functioning (DIF) analyses confirmed that there were no differences in the measurement results of the scale concerning gender. Additionally, Openness to Experience was found to be positively related to the CSE scale scores, providing some support for the scale’s convergent validity. Collectively, these results confirmed the psychometric soundness of the CSE scale for measuring creative self-efficacy and also identified avenues for future research.